ANALISIS RASIO LIKUIDITAS PADA PT. INDONESIA PRIMA PROPERTY, TBK - Hariyanti Hariyanti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The aim of this study is to determine the liquidity ratio of PT. Indonesia Prima Property Tbk. The type of used data is qualitative and quantitative data. The used data source is secondary data. The used analytical methods are liquidity ratios including current ratio, quick ratio, and cash ratio. The result of the study shows that the current ratio fluctuated 65.6% in 2015, 405.4% in 2016, and 175.6% in 2017. While for the quick ratio, it fluctuated in 2015 at 52.8%, in 2016 at 367.9% and in 2017 at 162.7%. For the cash ratio, it also fluctuated at 58.5% in 2015, 25.6% in 2016, and 19.3% in 2017. With these results, the hypothesis can be accepted.